Forward head in adults with headache - Ferracini, Gabriela Natália; Speciali, José Geraldo (Headache Medicine, 2013)
Background and objectives: Some musculoskeletal disorders of the cranio-cervical region, as head protrusion, decreased mobility and cervical myofascial trigger points, have been studied in subjects with headache. The protrusion of the head seems to be an antalgic posture and a factor perpetuating the headache, not a causative factor. The aim of this study was to review the literature regarding changes in the cervical spine and skull positioning in patients with headache. Content: We carried out a systematic search in bibliographic databases PubMed (National Library of Medicine), and Lilacs (Latin American and Caribbean Health Sciences) to identify relevant scientific studies. After analysis, eight met the criteria and were selected for this review, resulting in total of 51 papers, only eight articles met all the selection criteria, totaling 314 individuals, 128 with a diagnosis of chronic tension-type headache, 51 with headache episodic tension-type, 20 and 115 individuals with migraine without headache. Conclusion: The results of these studies suggest that individuals with migraine and tension-type headache (episodic and chronic) have more protrusion of the head than the controls without headache.